The Development of Sanggul Gala E-Modul at Beauty Study Program of Vocational High School - J, Kuswidyaningrum N.; Haryadi, Bambang; Widjanarko, Dwi (Journal of Vocational and Career Education, 2021)
The implementation of the Sanggul Gala learning is identical to the exploration of understanding, creativity, and imagination in order to produce a bun according to the desired theme. The limited references to books and modules, as well as the lack of Sanggul Gala learning media cause students' low understanding of the learning material. This is contrary to the factual condition, that vocational high school students in beauty study program are required to think critically and imaginatively in the Sanggul Gala learning process. The research questions of the present study are: 1) How is the development of Sanggul Gala e-Modul? and 2) how effective is the Sanggul Gala e-Modul in increasing the creativity of students in beauty study program?. The aims of this research are: 1) developing Sanggul Gala e-Modul; and 2) testing its effectiveness in increasing the creativity of beauty study program students. The research uses the RD (Research and Development) method referring to the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research sample was students Beauty Study Program of SMK Negeri 1 Tegal. Based on the results of the validation of learning media experts, it was found that the results of the development of the Sanggul Gala e-Module learning media had met the following criteria: 1) validity level: 81.67% (valid); 2) the level of feasibility: 3.56 (feasible), (3) the level of reliability; 0.364 (reliable). At the trial stage of the Sanggul Gala eModul and the video for students of beauty study program, it was found that the average score of students increased by 29.7% in all aspects (cognitive, affective and psychomotor). This shows that the Sanggul Gala e-Modul learning media is significant in improving the cognitive, affective and psychomotor aspects of students in beauty study program.